2004
DOI: 10.1248/cpb.52.1148
|View full text |Cite
|
Sign up to set email alerts
|

Two Cangorosin A Type Triterpene Dimers from Maytenus chuchuhuasca

Abstract: Two new cangorosin A type triterpene dimers, which composed of two triterpene units jointed by two ether linkages between the A and B rings, were isolated from the Brazilian medicinal plant "xuxuá" (Maytenus chuchuhuasca). Structures of new isolates, xuxuasins A (1) and B (2), were established based on several spectroscopic evidences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…5 The main difference was the absence of Me-23. The HMBC correlations spectrum (Figure 3) together with the 13 C NMR and DEPT data (Table 2) agreed with 6 being 23-nor-blepharodol.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…5 The main difference was the absence of Me-23. The HMBC correlations spectrum (Figure 3) together with the 13 C NMR and DEPT data (Table 2) agreed with 6 being 23-nor-blepharodol.…”
Section: Resultssupporting
confidence: 55%
“…The 1 H NMR, 13 C NMR, and DEPT spectra revealed that 7 was a sesquiterpenetriterpene adduct. 18,43 Its 1 H NMR spectrum presented signals characteristic of a triterpenic unit related to the isotingenol series: 49 five methyl groups, one doublet methyl (δ 1.00, J ) 5.9 Hz), two vinylic protons at δ 6.67 (1H, dd, J ) 9.8, 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations